Opportunistic predation by crested owl Lophostrix cristata upon Seba's Short-tailed bat Carollia perspicillata - Rocha, Ricardo (2014)
This note reports two opportunistic events of predation on Seba's Short-tailed Bats Carollia perspicillata (Chiroptera: Phyllostomidae) by an immature Crested Owl Lophostrix cristata (Strigiformes: Strigidae), in Central Amazonia, Brazil. Both predation events took place while bats were mist-netted. Given the abundance of C. perspicillata in the study area we argue that this bat species likely constitutes a natural prey for L. cristata.